Diversification of bamboo rats in Amazon rainforest (Dactylomys, Echimyidae, Rodentia): a phylogenomic and ecomorphologic approach - Silva, Heitor Bissoli (2024)
Dactylomys is a genus of bamboo rats from South America, widely distributed in the Amazon and adjacent regions (known as ratos-toró or coró). These arboreal rodents have striking characteristics, including elongated fingers, vibrant colors, vocalization capability, and a high association with bamboo in both várzea and terra-firme forests. While relationships at higher taxonomic levels within the Echimyidae family have been extensively explored, investigations at lower taxonomic levels, especially at the species level, remain limited, with widely distributed clades requiring attention, such as Dactylomys. This study employed a Museomic approach to investigate the diversification of Dactylomys across a broad distribution in the Amazon and parts of the Cerrado, spanning habitats from high altitudes to várzea and terra-firme forests. Through the generation and analysis of complete mitogenomes and 23 nuclear genes from 60 samples, morphological data from 186 specimens (107 adult skulls), this study aimed to assess the evolutionary relationships of bamboo rats of the genus Dactylomys (Rodentia: Echimyidae) employing an interdisciplinary approach integrating molecules, morphology, and ecology. Here I provide a new phylogeny for the genus based on mitogenomes and nuclear genes, revealing the presence of three major genetic lineages: a group from Peruvian and Bolivian highlands, a group from the southwest Amazon, and a group from central-northern South America. Additionally, this study identified new genetic variants, including a potential new taxon from the Rio Abiseo region. Population genetic analysis points to the greater importance of mitogenomes for inferring admixture patterns and clustering inference for Dactylomys, which may be related to the recent history of diversification of these rodents. Furthermore, analysis of ecological and morphological variation highlighted the adaptive plasticity of populations, with variations not always reflecting genetic structure. Within Dactylomys lineages occurring at higher elevations, smaller body sizes are observed, and an altitudinal gradient is likely linked to the evolution and dispersal of Dactylomys lineages in South America. The results also suggest transitions between different biomes and ecoregions, particularly in response to environmental changes and with the importance of dispersal routes. Additionally, the discovery of cranial cavities (sinuses) in Dactylomys and Kannabateomys represents a new morphological tool for ecological and evolutionary studies, with potential implications for systematics, macroevolution, and the ecology of living and fossil rodents. Additionally, some comments on the taxonomy of Dactylomys were provided, including new restrictions on the type locality.